Efficient electrocatalytic acetylene semihydrogenation by electron–rich metal sites in N–heterocyclic carbene metal complexes - Lei Zhang (Nature Portfolio, 2021)
This study explores N–heterocyclic carbene copper complexes toward selective electrocatalytic reduction of acetylene to ethylene. The electron–rich copper sites were found to facilitate acetylene adsorption and ethylene desorption and achieved high activity and selectivity for ethylene production.